2021
DOI: 10.17711/sm.0185-3325.2021.025
|View full text |Cite
|
Sign up to set email alerts
|

Smartphone addiction is associated with symptoms of anxiety, depression, stress, tension, confusion, and insomnia: A cross-sectional and comparative study with physically and non-physically active adults in self-isolation during the COVID-19 pandemic

Abstract: Introduction. During the novel coronavirus disease (COVID-19) outbreak, social media exposure and the use of electronic devices have increased; still, these behaviors may cause adverse health effects. Objective. This study assessed sleep quality, insomnia, mood, and psychological aspects among physically (n = 46) and non-physically (n = 53) active individuals during self-isolation throughout the COVID-19 pandemic and examined their association with smartphone addiction. Method. A cross-sectional study was cond… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 38 publications
1
1
0
Order By: Relevance
“…In another striking study on the subject, smartphone addiction increased during the pandemic period, which resulted in a decrease in the production of melatonin, which is considered an important hormone for the biological regulation of sleep, by smartphone light emitting short wavelengths. The study also found a significant correlation between insomnia severity indices 10 . Xiao et al 60 observed that as individuals became more socialized during the period of pandemic isolation, they slept better and became less stressed and anxious.…”
Section: Discussionsupporting
confidence: 56%
“…In another striking study on the subject, smartphone addiction increased during the pandemic period, which resulted in a decrease in the production of melatonin, which is considered an important hormone for the biological regulation of sleep, by smartphone light emitting short wavelengths. The study also found a significant correlation between insomnia severity indices 10 . Xiao et al 60 observed that as individuals became more socialized during the period of pandemic isolation, they slept better and became less stressed and anxious.…”
Section: Discussionsupporting
confidence: 56%
“…The type of population was categorized as follow: adolescents (6 studies) [ 71 , 81 , 87 , 92 , 108 , 138 ], children (1 study) [38], general population (66 studies) [ 40 , 42 , 43 , 46 , 48 , 49 ], [ [51] , [52] , [53] , [54] , [55] , [56] , [57] , 59 , 60 , [64] , [65] , [66] ], [ [68] , [69] , [70] , 72 , 73 , 76 , [78] , [79] , [80] ], [ [82] , [83] , [84] , [85] , 88 , 89 , 101 , 103 ], [ 104 , 109 , 110 , 113 , 117 , 120 , 121 ], [ 123 , 128 , 129 , 131 , 134 , 135 , 137 ], [ 139 , [141] , [142] , [143] , [144] , [145] , 147 , [150] , [151] , [152] ], [ 154 <...…”
Section: Resultsmentioning
confidence: 99%